2015
DOI: 10.1007/s10902-015-9620-1
|View full text |Cite
|
Sign up to set email alerts
|

Lay Understanding of Happiness and the Experience of Well-Being: Are Some Conceptions of Happiness More Beneficial than Others?

Abstract: The aim of the study was to understand aspects of life that men and women associate with happiness and to explore the connections between these associations and well-being (measured as positive affect, negative affect and life satisfaction) in different periods of life. Participants were 785 people who were asked to list associations that came to mind on hearing the word 'happiness'. The moderating roles of gender and period of life (adolescence/adulthood, transition/no transition) were analysed. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 56 publications
4
44
0
6
Order By: Relevance
“…Therefore, identifying age and gender differences in lay theories was not possible. This may be important because at least in adults and adolescents, there are age and gender differences in lay theories (Bojanowska and Zalewska 2016). Furthermore, students' responses may be influenced by the physical presence of their peers and teachers, as well as the responses on the WOWs written prior to their contribution.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, identifying age and gender differences in lay theories was not possible. This may be important because at least in adults and adolescents, there are age and gender differences in lay theories (Bojanowska and Zalewska 2016). Furthermore, students' responses may be influenced by the physical presence of their peers and teachers, as well as the responses on the WOWs written prior to their contribution.…”
Section: Limitationsmentioning
confidence: 99%
“…Lay theories of happiness, and their relationship with the positive affect people experience, differ between adults and adolescents (Bojanowska and Zalewska 2016). Additionally, Dube et al (1998) reported that both young adults and their parents believe that internal factors influence subjective well-being more than external factors, however parents attribute a greater role to external factors than do young adults.…”
mentioning
confidence: 99%
“…La problemática cobra relevancia dado que las concepciones o paradigmas por medio del cual los sujetos definan su felicidad los lleva a implicarse en diversas acciones o actividades, actividades que contribuirán finalmente a sus niveles de felicidad o bienestar (Bojanowska & Zalewska, 2015). El presente estudio se propuso contribuir a esta línea de investigación, indagando por un lado qué paradigmas son tenidos en cuenta por los ciudadanos a la hora de definir la felicidad y, por otra parte, verificar si los sujetos varían en sus niveles de felicidad subjetiva en función de cómo hayan definido el concepto de felicidad, ya sea desde un paradigma más hedónico o primordialmente eudaimónico.…”
Section: Discussionunclassified
“…Dado que cuando se habla de las concepciones de la felicidad se está haciendo referencia a una representación cognitiva individual de la naturaleza y experiencia del bienestar (Bojanowska & Zalewska, 2015), esta técnica resulta especialmente útil. En este sentido, la misma permite conocer el significado que los sujetos tienen sobre un concepto dado (Valdez, 2002).…”
Section: Instrumentosunclassified
See 1 more Smart Citation